From personality types to social labels: the impact of using MBTI on social anxiety among Chinese youth - Wu, Wenjing; Hao, Wenzhu; Zeng, Gao; Du, Weiyi (Frontiers in Psychology, 2024)
Introduction As the Myers-Briggs Type Indicator (MBTI) gains popularity among Chinese young people, it has undergone a gradual transition from being perceived as a personality assessment tool to being regarded as a social label. The objective of this study was to ascertain whether the use of the MBTI as a social label has an impact on social anxiety among Chinese youth groups. Methods A questionnaire survey was conducted on social media platforms to recruit Chinese youth aged 18 to 35. A total of 247 males and 222 females participated in the study, and the data was analyzed quantitatively using SPSS software and the Process macro plugin. Results The study found no strong correlation between MBTI as a social label and social anxiety. Moreover, this study introduced ego identity, belonging, and impression management as mediating variables and found that, under the influence of ego identity and impression management, the use of MBTI has a significant impact on social anxiety. Discussion The research reveals the complex role of MBTI among Chinese youth and provides a new perspective for understanding the impact of online social labels on the mental health of youth groups. Of course, this study also has limitations in terms of sample size and variable control. Future research should expand the sample size, introduce more potential influencing factors, and further validate and expand the existing conclusions.